Role of enhanced vector transmission of a new West Nile virus strain in an outbreak of equine disease in Australia in 2011 - van den Hurk, Andrew F (Parasit Vectors, 2014)
BACKGROUND: In 2011, a variant of West Nile virus Kunjin strain (WNV(KUN)) caused an unprecedented epidemic of neurological disease in horses in southeast Australia, resulting in almost 1,000 cases and a 9% fatality rate. We investigated whether increased fitness of the virus in the primary vector, Culex annulirostris, and another potential vector, Culex australicus, contributed to the widespread nature of the outbreak. METHODS: Mosquitoes were exposed to infectious blood meals containing either the virus strain responsible for the outbreak, designated WNV(KUN2011), or WNV(KUN2009), a strain of low virulence that is typical of historical strains of this virus. WNV(KUN) infection in mosquito samples was detected using a fixed cell culture enzyme immunoassay and a WNV(KUN)- specific monoclonal antibody. Probit analysis was used to determine mosquito susceptibility to infection. Infection, dissemination and transmission rates for selected days post-exposure were compared using Fisher’s exact test. Virus titers in bodies and saliva expectorates were compared using t-tests. RESULTS: There were few significant differences between the two virus strains in the susceptibility of Cx. annulirostris to infection, the kinetics of virus replication and the ability of this mosquito species to transmit either strain. Both strains were transmitted by Cx. annulirostris for the first time on day 5 post-exposure. The highest transmission rates (proportion of mosquitoes with virus detected in saliva) observed were 68% for WNV(KUN2011) on day 12 and 72% for WNV(KUN2009) on day 14. On days 12 and 14 post-exposure, significantly more WNV(KUN2011) than WNV(KUN2009) was expectorated by infected mosquitoes. Infection, dissemination and transmission rates of the two strains were not significantly different in Culex australicus. However, transmission rates and the amount of virus expectorated were significantly lower in Cx. australicus than Cx. annulirostris. CONCLUSIONS: The higher amount of WNV(KUN2011) expectorated by infected mosquitoes may be an indication that this virus strain is transmitted more efficiently by Cx. annulirostris compared to other WNV(KUN) strains. Combined with other factors, such as a convergence of abundant mosquito and wading bird populations, and mammalian and avian feeding behaviour by Cx. annulirostris, this may have contributed to the scale of the 2011 equine epidemic.